Identificação de Neutrophil Extracellular Traps em lesões tegumentares de pacientes com Paracoccidiodomicose e análise da formação de NETs in vitro por neutrófilos humanos desafiados com Paracoccidioides brasiliensis - Coletta, Amanda Manoel Della [UNESP] (2014)
Paracoccidiodomycosis (PCM), an endemic systemic mycosis in Latin America, is caused by the thermodimorphic fungus of Paracoccidioides genus (Paracoccidioides brasiliensis (Pb) and Paracoccidoides lutzii). Recently, works in PCM have focused the role of neutrophils (PMNs), since literature has demonstrated the dynamic involvement of these cells in host defense against microorganisms. Studies have shown that PMNs could use a novel strategy to destroy microorganisms (NETosis), a type of neutrophil death distinct from apoptosis and necrosis. This mechanism involves the release of extracellular traps by activated neutrophils, known as neutrophil extracellular traps (NETs). It has been proposed that NETs may destroy microorganisms that were not phagocytosed by neutrophils, and this could be proposed for Pb, since the fungus yeast can present different sizes. In this context, the objectives of this study were identify the presence of NETs in vivo and in vitro, analyzing samples of patients with PCM by different methodologies. Tissue sections from formalin-fixed biopsies were stained with DAPI, anti-elastase (FITC) and anti-histone (Texas-Red) for confocal immunofluorescence microscopy analysis, and with Hematoxylin-Eosin (H&E) for histopathology. Neutrophil cultures were challenged with two isolates of Pb (Pb18 and Pb265), analyzed by scanning electron microscopy and NETs were quantified by the Picogreen dsDNA kit. The images revealed the presence of NETs constituents, nuclear and extracellular localization of DNA, co-localization of elastase and histone, confirmed by the overlay of the three stains. Histopathology showed the presence of Pb and inflammatory infiltrate with high number of neutrophils on the site of the lesion and extracellular DNA (hematoxylin positive) indicating NETs. Both isolates were able to induce NET release in vitro in similar levels. Thus, P. brasiliensis (Pb18 and Pb265) is able to induce NETs formation by ...